Expresión gráfico plástica y su relación con la imaginación en los niños de la Institución Educativa Inicial N°733, Ramón Castilla 2023 - Sinarahua Torres, Rosa Elena (2024)
The central purpose of this study was to establish the level of relationship between plastic graphic techniques and imagination in the children of the Institución Educativa Inicial N°733 Ramón Castilla 2023. In order to achieve this objective, a quantitative approach of a nature was adopted. relational, and a non-experimental, specifically correlational and transversal design was chosen. The population under study included all boys and girls of both genders, and a representative sample of 112 participants was constituted. As instruments for data collection, observation techniques were used, supported by an observation guide, and the data obtained were validated through expert evaluation. It is concluded that there is no significant relationship between plastic graphic expression and imagination in children. Furthermore, considering a correlation value of the Rho Spearman test is 0.166, we can affirm that this relationship is low.